BacTracker mobile app - Mustafa Kamil, Afiqah; Amdan, Nur Hafizah; Ahmad Shukri, Nur Shahirah; Mohamed Jamaludin, Mohamed Alif; Saad, Wan Zuhainis (UTM Academic Leadership (UTMLead), Universiti Teknologi Malaysia, 2016)
Learning about microbes can be fun through mobile app especially those microbes that may be found on you or with you. BacTracker provides platform to explore and enhance learning of microbes that may be present in your lives focusing on cosmetics.